Examining The Application Of Standard Of Proof In Criminal Cases: A Comparative Analysis Of Islamic Law And Common Law In Malaysia - Suhaizad Saifuddin; Hanifah Haydar Ali Tajuddin; Mohamad Azhan Yahya; Mohamad Rizal Abd Rahman; Fatimah Yusro Hashim (USIM PRESS, 2024)
Malaysian Journal of Syariah and Law (MJSL) Volume 12 Issue 1 Page (11-22)